(3ejRGf GdeYOdI aj TCf GdHSedIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai , bO ETJgQ cdGe GdfGS ai GdHSedI hEMJLGLge Ydi CfgG bQBf hZjQ bQBf hTfY GdbGVi CHh HcQi GdHGbdGfi hZjQg Ydi GdTGaYi ai EKHGJgG bQBfkG s
(3BNQgG (B:s
(3hGdPi faSi HjOg Cfi dGTHgce UdGI HQShd Gddg Udi Gddg Ydjg hSde gPG MOjK UMjM dGYdI dg hgh CUM eG hQO ai GdHGH Hd de jUM ajg MjK ZjQg hCNQL GdMGce ai GdeSJOQc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HBNQgG hbaI cGJHs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1918s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds